MOBILITAS TENAGA KERJA PEREMPUAN DI KELURAHAN TARA-TARA DUA KOTA TOMOHON - Arsilfa Nurjana Mokoagow; O. Esry. H. Laoh; Jean F. J. Timban (Sam Ratulangi University, 2017)
This study aims to determine the social mobility of female workers in Tara-tara Dua Village, Tomohon City. The research was conducted for 4 months, from February until May 2017. The data collected in this research are primary data and secondary data. Primary data was obtained from interview to the respondents’ ie female labor based on the prepared list of question. Secondary data obtained by Tara-tara Dua Village Office, Tomohon City. Analysis of data used in this research is Descriptive Analysis, where the data collected will be presented in tabular form. The results show that upward vertical social mobility on the type of housekeeper's job is to be a cake seller, food seller, selling rice, stall owner. When viewed from the previous occupation as rice farmers there is a vertical mobility that upward mobility with the supporting income and the more promising types of jobs as household servants, cooperative employees, stall owners, State Civil Servants (ASN), vegetable traders in the market, village equipment, and rice sellers.